2003
DOI: 10.1074/jbc.m305488200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Involvement of Protein Myristoylation in Myristoylated Alanine-rich C Kinase Substrate (MARCKS)-Calmodulin Interaction

Abstract: MARCKS, a major in vivo substrate of protein kinase C, interacts with plasma membranes in a phosphorylation-, myristoylation-, and calmodulin-dependent manner. Although we have previously observed that myristoylated and non-myristoylated MARCKS proteins behave differently during calmodulin-agarose chromatography, the role of protein myristoylation in the MARCKS-calmodulin interaction remained to be elucidated. Here we demonstrate that the myristoyl moiety together with the N-terminal protein domain is directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…Additional electrostatic interactions were also shown to stabilize CaM-protein interactions (44,45,50,51). However, the importance and relative contribution of hydrophobic versus electrostatic factors in myr(ϩ)MA⅐CaM interactions are not known, especially that the hydrophobic myr group can potentially play a role as was observed in other CaM-protein interactions (44,45,50,51). ITC has been used to determine the affinity and thermodynamic parameters of CaM binding to myr(ϩ)MA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional electrostatic interactions were also shown to stabilize CaM-protein interactions (44,45,50,51). However, the importance and relative contribution of hydrophobic versus electrostatic factors in myr(ϩ)MA⅐CaM interactions are not known, especially that the hydrophobic myr group can potentially play a role as was observed in other CaM-protein interactions (44,45,50,51). ITC has been used to determine the affinity and thermodynamic parameters of CaM binding to myr(ϩ)MA.…”
Section: Resultsmentioning
confidence: 99%
“…Myristate Group of MA Is Not Required for CaM BindingSeveral myristoylated proteins including MARCKS, CAP-23/ NAP-22, and HIV-1 Nef were found to bind CaM to facilitate their intracellular localization and membrane targeting (44,45,50,51). Our ITC data described above show that CaM binding to myr(ϩ)MA is entropically driven, indicating a major contribution of hydrophobic contacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this region is poorly understood in AKAPs, the MARCKS protein-like domain has the potential for providing strong binding to membrane phospholipids, may sequester PtdIns(4,5)P 2 , and, as mentioned above, is certainly a putative binding site of CaM influenced by protein N-myristoylation of MARCKS protein [36]. In AKAP79, the sequence K 31 ASMLC-FKRRKKAAKALKPKAG 52 (where the bold residues represent the dibasic residue motif) also has been implicated as a CaMbinding domain, as well as a weak PKCβII-binding site [37].…”
Section: Marcks Protein Membrane Effector-like Domainmentioning
confidence: 99%
“…2C, D, and E). Considering that N-terminal myristoylation of MARCKS is partially involved in membrane binding, 25 such lipidation may prevent membrane dissociation of the protein from enzymatic activity. However, in cells treated with myristoylation inhibitor 2-hydroxymyristic acid (2-HM), the parallel experiments performed under the same condition showed that de-myristoylation did not affect the location of MARCKS (Fig.…”
Section: Depletion Of Poly-pis Induces Cytosolic Translocation Of B2ementioning
confidence: 99%